Pengaruh Struktur Modal dan Ukuran Perusahaan Terhadap Nilai Perusahaan pada Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia Tahun 2018 – 2022 - Rizky Abdhul Kharim; Hwihanus Hwihanus (Akuntansi, 2024)
This study aims to determine the effect of capital structure, and company size on firm value. The population in this study are cigarette companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling method was purposive sampling so that a total sample of 5 companies was obtained. The data analysis technique uses multiple linear regression analysis. The results in this study indicate that capital structure has an effect on firm value, while company size has no effect on firm value.